Challenges and perspectives in the diagnosis of extrapulmonary tuberculosis. Issue 5 (May 2014) - Norbis, Luca; Alagna, Riccardo; Tortoli, Enrico; Codecasa, Luigi Ruffo; Migliori, Giovanni Battista; Cirillo, Daniela M
<x xml:space="preserve">Abstract</x> Extrapulmonary tuberculosis (EPTB) accounts for a significant proportion of tuberculosis cases worldwide. Nevertheless, the diagnosis is often delayed or even missed due to insidious clinical presentation and poor performance of diagnostic tests. Culture, the classical gold standard for tuberculosis, suffers from increased technical and logistical constraints in EPTB cases. In this review the authors outline current diagnostic options for the main forms of EPTB. The authors also discuss the opportunities and challenges linked in particular to microbiological diagnostics and to the attempts to find a new gold standard test for EPTB. Finally, new biomarkers and tests currently under evaluation are hopefully on the way to introduce significant improvements in EPTB diagnosis, for which clinical suspicion will nevertheless be essential.